Occurrence and removal of microplastics in a hybrid growth sewage treatment plant from Bihar, India: A preliminary study. (20th November 2022) - Parashar, Neha; Hait, Subrata
Abstract: Sewage treatment plants (STPs) as a carrier of microplastics (MPs) have received considerable attention worldwide recently. In India, the majority of studies on MPs have been conducted in sediments, riverine, and marine systems, while knowledge on MPs occurrence in STPs is scarce. Henceforth, this work evaluated the presence of MPs in sewage and sludge in a hybrid growth, secondary treatment-based STP system. Optical microscopy, scanning electron microscopy (SEM), and Fourier-transform infrared (FTIR) spectroscopy methods were used to examine the abundance of MPs in raw sewage, effluent from different treatment units of the STP, and sludge samples. A total number of MPs of 201 ± 19 (2021) and 197 ± 22 (2022) were detected in the studied STP system. Results showed that MPs ranged between 64.3 ± 4.89–47.66 ± 4.71 n/L (sewage) and 1.14 ± 0.30–1.38 ± 0.65 n/g (sludge) with the overall removal efficacy of the studied STP estimated to be around 80%. Fragments and fibers were predominant among all shapes and particles mostly belonged to sizes <50 μm and <50 μm–250 μm in sewage and sludge, respectively. In total, seven polymers were identified of which low-density polyethylene (LDPE) constituted the highest proportion in sewage (26%–31%) and polyvinyl chloride (PVC) contributed the highest in the sludge (22%–27%). Moreover, MPs control measures have been discussed based on the findings of this study to restrict MPs re-entry into the environment via treated effluent and sludge. Graphical abstract: Image 1 Highlights: First study on MPs occurrence and removal in a hybrid growth MBBR-based STP. Around 80% MPs were removed via the primary and secondary treatment stages in the STP. LDPE (in sewage) and PVC (in sludge) were the most prevalent polymers. Small-sized MPs (<250 μm) like fragments and fibers were predominant shapes. Advanced treatment options for MPs removal from secondary-treated effluent discussed.